Similar patterns of age-specific reproduction in an island and mainland population of great tits Parus major - Bouwhuis, S; van Noordwijk, A; Sheldon, B; Verhulst, S; Visser, M (2010)
The process of ageing was long thought to be too infrequent to affect life-histories in natural populations. Long-term studies have, however, recently demonstrated ageing to be ubiquitous even in the wild, although confounding factors, such as emigration instead of mortality, or inter-population variation in rates of ageing have seldom been addressed. Here, we present analyses of female age-specific reproductive performance in a Dutch island population of great tits Parus major. For this population with limited connectivity to surrounding areas, we show that, between individuals, reproductive lifespan positively co-varies with recruit production, while within individuals performance improves up to 3 years of age, after which it gradually declines. We also show these patterns to be strikingly similar to those recently found in a less isolated British mainland population of great tits, characterised by different environmental conditions and life-history strategies, in particular the frequency of multiple breeding. Our results therefore suggest patterns of age-specific reproductive performance to be robust to both environmental and life-history variation. © 2010 The Authors.